2008
DOI: 10.1021/jf8005239
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Spectroscopy Interference Effects of β-Carotene and Lycopene by Neural Networks

Abstract: In this study a new computerized approach and linear models (LMs) to solve the UV/vis spectroscopy interference effects of beta-carotene with lycopene analysis by neural networks (NNs) are considered. The data collected (absorbance values) obtained by UV/vis spectrophotometry were transferred into an NN-trained computer for modeling and prediction of output. Such an integrated NN/UV/vis spectroscopy approach is capable of estimating beta-carotene and lycopene concentrations with a mean prediction error 50 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although there is a need in the food industry to improve quality and process controls, the application of LIBS technique in food control analysis has not been sufficiently explored and only few studies can be found in literature (Bilge, Boyacı, Eseller, Tamer, & Çakır, 2015;Bilge, Sezer, Eseller, Berberoglu, Topcu, & Boyaci, 2016;Bilge, Velioglu, Sezer, Eseller, & Boyaci, 2016;Mbesse Kongbonga, Ghalila, Onana, & Ben Lakhdar, 2014). The combination of LIBS with chemometric methods offers the possibility to be used in a fast, automatic and on-line manner as has already been demonstrated with successful results for sample classification and quantification (Caceres, Moncayo, Rosales, de Villena, Alvira, & Bilmes, 2013;Curteanu & Cartwright, 2011;Huang, Kangas, & Rasco, 2007;Moncayo, Manzoor, Navarro-Villoslada, & Caceres, 2015;Moncayo, Rosales, Izquierdo-Hornillos, Anzano, & Caceres, 2016;Torrecilla, Cámara, Fernández-Ruiz, Piera, & Caceres, 2008). Some authors have shown that the molecular LIBS signal is dependent on the molecular nature of the sample (Anzano, Casanova, Bermúdez, & Lasheras, 2006;Gregoire, Boudinet, Pelascini, Surma, Detalle, & Holl, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a need in the food industry to improve quality and process controls, the application of LIBS technique in food control analysis has not been sufficiently explored and only few studies can be found in literature (Bilge, Boyacı, Eseller, Tamer, & Çakır, 2015;Bilge, Sezer, Eseller, Berberoglu, Topcu, & Boyaci, 2016;Bilge, Velioglu, Sezer, Eseller, & Boyaci, 2016;Mbesse Kongbonga, Ghalila, Onana, & Ben Lakhdar, 2014). The combination of LIBS with chemometric methods offers the possibility to be used in a fast, automatic and on-line manner as has already been demonstrated with successful results for sample classification and quantification (Caceres, Moncayo, Rosales, de Villena, Alvira, & Bilmes, 2013;Curteanu & Cartwright, 2011;Huang, Kangas, & Rasco, 2007;Moncayo, Manzoor, Navarro-Villoslada, & Caceres, 2015;Moncayo, Rosales, Izquierdo-Hornillos, Anzano, & Caceres, 2016;Torrecilla, Cámara, Fernández-Ruiz, Piera, & Caceres, 2008). Some authors have shown that the molecular LIBS signal is dependent on the molecular nature of the sample (Anzano, Casanova, Bermúdez, & Lasheras, 2006;Gregoire, Boudinet, Pelascini, Surma, Detalle, & Holl, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in carotenoids as bioactive food components has promoted the development of numerous rapid methods for their measurement in tomato and tomato products, which are the main source of carotenoids in the western diet (Giovannucci, 2002). Techniques such as UV-vis (Choudhary et al, 2009;Pflanz and Zude, 2008;Torrecilla et al, 2008), near-infrared (Clé ment et al, 2008;Kusumiyati et al, 2008;Pedro and Ferreira, 2005), mid-infrared (De Nardo et al, 2009;Halim et al, 2006;Rubio-Diaz et al, 2010) and Raman (Bhosale et al, 2004;Schulz et al, 2005) spectroscopy have been frequently proposed as alternatives to HPLC for the simple, high-throughput and costeffective analysis of tomato carotenoids. The selection of the most adequate spectroscopic method will depend on the objective of the analysis, characteristics of the sample, expected accuracy and specificity, and equipment amenability.…”
Section: Introductionmentioning
confidence: 99%
“…However, neural networks (Torrecilla et al, 2008) and iterative multiple linear regression analysis (Pflanz and Zude, 2008) have been shown to improve the performance of UV-vis spectroscopy for the measurement of lycopene and b-carotene in regular tomatoes. The analysis of new tomato varieties with complex profiles of carotenoids in various isomeric configurations requires methods with higher degrees of specificity.…”
Section: Introductionmentioning
confidence: 99%
“…New computerized approaches and linear models (LMs) to solve the UV/ visible spectroscopy interference effects of b-carotene with lycopene analysis by neural networks (NNs) have been reported in recent years [236,237]. The data (absorbance values) obtained by UV/visible spectrophotometry were transferred to an NN-trained computer for modeling and prediction of output.…”
Section: Uv/visible Spectroscopymentioning
confidence: 99%